Luaran Bayi dari Ibu dengan Tuberkulosis Resistan Multi Obat - Yusuf, Dwiyanarsi; Lisnawati, Yuyun (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: Multidrug-resistant TB (MDR-TB) is described as Mycobacterium tuberculosis infection resistant to rifampicin and isoniazide with or with-out resistance to other drugs. MDR-TB, if left untreated or undiagnosed inpregnancy, is associated with higher maternal morbidity, mortality, and increased risk of vertical transmission. There are increased risk of obstetrical complications like spontaneous abortions, fetal growth restriction, oligohydram-nios, preterm labor and increased neonatal mortality. Objective: This study was intended to present a case series of MDR-TB treat-ment among pregnancies and fetal outcome in our hospital. Methods: Evaluation of 3 pregnant woman who had been diagnosed with MDR-TB. Data were obtained by history taking, physical examinations, laboratory results and outcome of the neonates. Results: Two out of 3 pregnant woman were known resistant to rifampicin andwere given ethionamide and levofloxacin for more than a month. C-sectionwere performed in all pregnancies at 32 weeks, 36 weeks and 36 weeks withbaby weight 1450 gr, 2350 gr, and 2600 gr respectively. There was no congeni-tal abnormality found in all neonates. Conclusion: Case series of MDR-TB in pregnancy has been reported. Two outof 3 patients were received ethionamide and levofloxacin treatment during pregnancy, showed no deformity or congenital abnormality in the neonates. Low birth weight neonates were found in two patients.